The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1902/jop.2013.134001
|View full text |Cite
|
Sign up to set email alerts
|

Academy Report: Peri‐Implant Mucositis and Peri‐Implantitis: A Current Understanding of Their Diagnoses and Clinical Implications

Abstract: The American Academy of Periodontology (AAP) periodically publishes reports, statements, and guidelines on a variety of topics relevant to periodontics. These papers are developed by an appointed committee of experts, and the documents are reviewed and approved by the AAP Board of Trustees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(88 citation statements)
references
References 65 publications
1
82
0
Order By: Relevance
“…Methodological development is undertaken using a ‘case-study’ application of biofilm disruption on Titanium (Ti) dental implants which possess a variety of surface topologies ranging from highly polished through to complex tortuous surfaces engineered to promote osseo-integration28. Ti dental implants are susceptible to peri-implant inflammation (peri-implantitis) driven by the presence of a surface biofilm and which leads to loss of bony integration and ultimately implant failure2930. Removal of biofilm from dental implants is difficult and many methods damage the surface.…”
mentioning
confidence: 99%
“…Methodological development is undertaken using a ‘case-study’ application of biofilm disruption on Titanium (Ti) dental implants which possess a variety of surface topologies ranging from highly polished through to complex tortuous surfaces engineered to promote osseo-integration28. Ti dental implants are susceptible to peri-implant inflammation (peri-implantitis) driven by the presence of a surface biofilm and which leads to loss of bony integration and ultimately implant failure2930. Removal of biofilm from dental implants is difficult and many methods damage the surface.…”
mentioning
confidence: 99%
“…Four of the included studies were papers from consensus conferences [18-20,23]; two of them suggested diagnostic guidelines [24,25], three authors suggested the classification of peri-implantitis [3,21,26], and another suggested the index of implant success (Table 1) [22]. …”
Section: Resultsmentioning
confidence: 99%
“…Peri-implant mucositis has been defined as a reversible inflammatory reaction of peri-implant soft tissues with no radiographic evidence of bone loss [1]. From a clinical perspective, signs that determine the presence of peri-implant mucositis include erythema and swelling, usually associated with probing depths ≥4 mm [23]; however, the essential parameter for diagnosis is bleeding on gentle probing (<0.25 N) [4]. In contrast, peri-implantitis has been identified as a progressive and irreversible infectious pathological condition associated with changes in the level of crestal bone, the presence of bleeding on probing (BOP), and/or suppuration with or without concomitant deepening of the peri-implant pockets around an osseointegrated implant in function [45].…”
Section: Introductionmentioning
confidence: 99%